The Importance of Applying Educational Philosophy by Elementary School Teachers - Elbi Rosyid, Farhan; Neviyarni; Zen, Zelhendri (Universitas Ahmad Dahlan, 2025)
Philosophy of education plays a crucial role in shaping the foundation of thinking and action for elementary school educators. Teachers are not only instructors but also character builders, moral guides, and agents of social transformation. This study employs a literature review method by analyzing previous research on implementing educational philosophy in elementary education. The findings reveal that applying various philosophical perspectives—such as progressivism, idealism, essentialism, and perennialism provides clear direction for the learning process and supports the development of students’ critical thinking, reflective abilities, and integrity. Therefore, mastering the philosophy of education is essential for teachers to create meaningful, value-based, and future-oriented learning experiences.